Synthesis and Characterization of Oligomer Bis(trans-2,3-dibromo-4-hydroxy-2-butenyl)terephthalate as a Green Corrosion Inhibitor on Mild Steel in 1 M H3PO4 Solution - Rasha Jasim Tuama (Indonesian Journal of Chemistry, 2023)
Poly(ethylene terephthalate) (PET) waste was depolymerized by trans-2,3-dibromo-2-butene-1,4-diol in the presence of manganese acetate as a catalyst using microwave irradiation as opposed to the conventional heating process in order to reduce the time required for PET depolymerization. The depolymerization product bis(trans-2,3-dibromo-4-hydroxy-2-butenyl)terephthalate (BDBHBT) was isolated, characterized, and evaluated as a green inhibitor for mild corrosion steel in corrosive 1 M H3PO4 medium. This product was characterized using FTIR and 1H-NMR. The effects of immersion time, inhibitor concentration, and reaction temperature were studied. The chemical technique utilized in this study was weight loss, while the electrochemical technique employed an open circuit potential. With 0.6 g/L of BDBHBT inhibitor, the highest corrosion inhibition efficiency of 83.3% was observed. The kinetic and thermodynamic functions were calculated, and the results indicated that the investigated inhibitor was physically adsorbed on the surface and confirmed to the Langmuir adsorption isotherm. This study aims to lessen pollution of the environment by transforming PET waste to a beneficial oligomer BDBHBT and estimating the inhibitory effect of this product on the corrosion of mild steel in 1 M H3PO4.